Two ZnII mononuclear coordination compounds with pyridinedicarboxylate and auxiliary N‐(pyridin‐4‐ylmethylidene)hydroxylamine ligands. Issue 12 (5th November 2014) - Coropceanu, Eduard B.; Dreab, Ana; Croitor, Lilia
<x xml:space="preserve">Abstract</x> Two new mononuclear coordination compounds, bis{4‐[(hydroxyimino)methyl]pyridinium} diaquabis(pyridine‐2, 5‐dicarboxylato‐κ2N, O2)zincate(II), (C6H7N2O)2[Zn(C7H3NO4)2(H2O)2], (1), and (pyridine‐2, 6‐dicarboxylato‐κ3O2, N, O6)bis[N‐(pyridin‐4‐ylmethylidene‐κN)hydroxylamine]zinc(II), [Zn(C7H3NO4)(C6H6N2O)2], (2), have been synthesized and characterized by single‐crystal X‐ray diffractometry. The centrosymmetric ZnII cation in (1) is octahedrally coordinated by two chelating pyridine‐2, 5‐dicarboxylate ligands and by two water molecules in a distorted octahedral geometry. In (2), the ZnII cation is coordinated by a tridentate pyridine‐2, 6‐dicarboxylate dianion and by two N‐(pyridin‐4‐ylmethylidene)hydroxylamine molecules in a distorted C2‐symmetric trigonal bipyramidal coordination geometry.